Inverse association between positive tuberculin tests and positive allergy skin tests in children - Nur Rochmah; Dyahris Kuntartiwi; Anang Endaryanto; Aryanto Harsono (Indonesian Pediatric Society, 2009)
Background The association between Mycobacterium tuberculosisinfection and atopy remains controversial. Reaction to tuberculosisinfection is mediated by Th-1 immune responses whereas allergicreactions are mediated by Th- 2 immune response. In patients withatopic syndrome who also suffer from tuberculosis infection, theTh-2 response will be suppressed and allergy manifestations willdecrease. Therefore, it is important to determine the appropriateallergy test and to predict outcome after completing tuberculosistreatment.Objective To evaluate the influence of a positive tuberculin teston skin test results in diagnosing atopic disease.Methods A cross sectional study was conducted in the pediatricallergy outpatient clinic, Soetomo Hospital, Surabaya, Indonesiabetween 2004 and 2007. Eighty-five patients were enrolled inthis study. The tuberculin test was performed on all patientswith allergy. The allergy test was carried out by performing a skinscratch test.Results There was a weak inverse correlation between positivetuberculin tests and positive allergy skin tests in children (housedust mite, food and pet allergies). The correlation between apositive tuberculin test and house dust mite allergy test wasr: -0.364 (P=O.OOl; a=O.Ol). The correlation between thetuberculin test and food allergies was r: -0.420 (P=O.OOl;a=O.Ol). The correlation between the tuberculin test and petallergies was r: -0.344 (P= 0.001; a=O.Ol).Conclusions A positive tuberculin test is weakly correlated withpositive allergy skin test results, suggesting that it is appropriate todo allergy skin testing even in children with a positive tuberculintest.